2011
DOI: 10.1002/ejoc.201100972
|View full text |Cite
|
Sign up to set email alerts
|

Selective Binding of Glyphosate by a Ditopic Cyclic–Open‐Chain Polyazaligand in Aqueous Solution

Abstract: International audienceThis paper reports a study of the interaction between a ditopic cyclic–open-chain polyazaligand L1py and the herbicide glyphosate [N-(phosphonomethyl)glycine or PMG] by potentiometric titrations as well as calorimetry and NMR measurements. This nonsymmetrical ligand is composed of a cyclam unit (1,4,8,11-tetraazacyclotetradecane) and the linear tetraamine 1,4,8,11-tetraazaundecane linked by a 2,6-dimethylpyridine spacer. This ligand forms stable adducts with PMG. For comparison, two analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 48 publications
(70 reference statements)
2
4
0
Order By: Relevance
“…8). 21,23 This result supports the hypothesis of an interaction mode involving binding of the phosphonate moiety of PMG to Zn(II) and highlights the relevant role played by the metal centre in the recognition process. 23…”
Section: Equilibriumsupporting
confidence: 76%
See 4 more Smart Citations
“…8). 21,23 This result supports the hypothesis of an interaction mode involving binding of the phosphonate moiety of PMG to Zn(II) and highlights the relevant role played by the metal centre in the recognition process. 23…”
Section: Equilibriumsupporting
confidence: 76%
“…Ligands L1py, L2py and L1para are synthesized according to previously described procedures. 22,23 A previous investigation on the L1py and L2py basicity properties showed that these ligands behave as polyprotic bases in aqueous solutions, forming a number of protonated species in the pH range 2-11. 22,23 For instance, at neutral pH, they form a tetraprotonated species, featuring two ammonium groups on the cyclam unit and the remaining couple on the open-chain tetraamine moiety.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations